Developing a Credit Reporting Framework in Kenya - Mwiti, Makena (World Bank, Washington, DC, 2012)
In 2000, the level of nonperforming loans in Kenya topped Kshs 112 billion (US$1.4 billion). This posed a threat to the stability of the financial sector, and there was a consensus that a credit information sharing mechanism would help resolve the tendency of some debtors to take advantage of information asymmetry and resort to multiple borrowing, thus becoming serial defaulters. After several failed initiatives by various local stakeholders to set up credit bureaus, International Finance Corporation (IFC) was invited to provide assistance to the government authorities in setting up a legal and regulatory framework as well as to support private sector operators.